Vaccinations of children against chickenpox and pneumococcal infection on the example of several family practice physicians’ settings - Bednarek, Anna; Mianowana, Violetta (Polish Journal of Public Health, 2015)
Introduction. Vaccinations against varicella and pneumococcal infection are an important form of prevention of infectious diseases and their possible complications. Aim. Assessment of the vaccination control of children against varicella, and pneumococcal infection based on selected institutions of family practice physician. Material and methods. There were verified 807 immunization cards of children from three vaccination offices, selected at random from the area of the southeastern Poland, i.e. the provinces of Lubelskie, Podkarpackie and Świętokrzyskie. Based on the results of quantitative analysis of medical records of vaccination carried out in these institutions through 2007-2012, the number of children vaccinated against varicella, and pneumococcal infection was assessed. Results. The largest number of vaccinated children (against pneumococcal infection – 148 children and 84 against varicella among 335 subjects reporting in the facility) was confirmed in health care unit in Lublin. In health care unit in Podkarpackie the number of vaccinated children against pneumococcal infection was 84 and against chicken pox – 52 among 256 children using the medical services. In health care unit in Świętokrzyskie, 65 children were vaccinated against pneumococcal infection and 34 against varicella among 216 subjects reporting at the institution. The vast majority of these vaccines (431 – including three centers) was paid by parents. Conclusions. 1. In all of the centers, a higher proportion of children was vaccinated against pneumococcal infection than chickenpox. 2. There was not a marked increase in the number of children vaccinated against varicella and pneumococcal infection during the analyzed period.